1997
DOI: 10.1021/la9605955
|View full text |Cite
|
Sign up to set email alerts
|

Dihedral Angle of Lens and Interfacial Tension of Air/Long Chain Alcohol/Water Systems

Abstract: The dihedral angle of an alcohol lens at the air/water interface and the three kinds of interfacial tensions of air/1-octanol/water and air/1-decanol/water systems have been measured as a function of temperature from 288.15 to 313.15 K at 2.5 K intervals under atmospheric pressure. In order to measure a dihedral angle, the new experimental apparatus was constructed and the new procedure was adopted. By comparing the dihedral angles measured with those calculated by applying Neumann's relations to the interfaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…Interfacial tension σ of 18-crown-6 and dicyclohexano-18-crown-6 at the air/water interface were measured by home made drop volume tensiometer [19] and those at hexane/water interface were measured by home made pendant drop tensiometer [20,21] at various concentrations and at 25.0 ± 0.1 • C. The estimated experimental error of σ was within ±0.05 mN/m. The equilibrium values of σ at air/water and hexane/water interfaces were obtained respectively after about 30 and 60 min later when the hanging drops were formed at the glass capillary tip.…”
Section: Methodsmentioning
confidence: 98%
“…Interfacial tension σ of 18-crown-6 and dicyclohexano-18-crown-6 at the air/water interface were measured by home made drop volume tensiometer [19] and those at hexane/water interface were measured by home made pendant drop tensiometer [20,21] at various concentrations and at 25.0 ± 0.1 • C. The estimated experimental error of σ was within ±0.05 mN/m. The equilibrium values of σ at air/water and hexane/water interfaces were obtained respectively after about 30 and 60 min later when the hanging drops were formed at the glass capillary tip.…”
Section: Methodsmentioning
confidence: 98%
“…[9] and [10] simultaneously and therefore is purely algebraic, and the other is to introduce undetermined multipliers (25). We employ the latter because it has been reported that it offers distinct physical meanings to the undetermined multipliers (25 [11] where the superscript indicates that a quantity with is the surface excess one introduced in Eq. [4] and is defined by…”
Section: Thermodynamic Equations As a Function Of Temperature Pressumentioning
confidence: 99%
“…[29] is reduced to Eq. [11] if v ,␥ is chosen to be zero. Now it is recognized that employing T, p ␣ , p ␤ , p ␥ , 4 , .…”
Section: The P Conventionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with that of Yeh et al, 17 which demonstrated that σ Rβ (n-C 6 E 0 ) > σ Rβ (n-C 5 E 0 ) > σ Rβ (n-C 4 E 0 ) and σ Rβ (n-C 5 E 0 ) > σ Rβ (2-C 5 E 0 ) > σ Rβ (t-C 5 E 0 ). It was suggested 15,16 that the longer hydrocarbon chains interact more strongly than the shorter ones in the alcohol-rich phase, and the transfer of alcohol molecules from bulk phase to the airliquid interface is energetically unfavorable for longer chain alcohols. Thus the iso-C 4 E 0 + water system provides lower surface tension σ Rβ due to its shorter "effective" chain length.…”
Section: Effect Of Hydrophobicity Of C I E J On Wetting Behavior Approaching the Upper Critical Solutionmentioning
confidence: 99%